Stefano Fenoaltea (1943-2020) - McCloskey, Deirdre (PSL Quarterly Review, 2021)
Obituary of Stefano Fenoaltea (1943-2020), economic historian and longtime collaborator of this journal. The author recalls her personal encounter with Stefano Fenoaltea and shortly but vividly summarizes his character and their friendship over the decades. JEL codes: B32, N13, N14